Graphene oxide supported oxidovanadium coordination compound as an efficient catalyst for the green oxidation of benzyl alcohol - Mohammadreza Aliniya; Rahman Bikas; Neda Heydari; Marta S. Krawczyk; Tadeusz Lis (Scientific Reports)
Abstract In this research, a green method for the oxidation of benzyl alcohol to its oxidized products has been reported. Firstly, (E)-4-amino-N’-(phenyl(pyridin-2-yl)methylene)benzohydrazide (HL) as an NNO-donor ligand was synthesized by the reaction of 2-benzoylpyridine and 4-aminobenzohydrazide in a molar ratio of 1:1 under reflux condition. HL was used for the synthesis of a V(V) coordination compound, [VO(µ-O)L]2, through its reaction with NH4VO3 in methanol under reflux condition and the orange crystals of dinuclear oxidovanadium(V) coordination compound, [VO(µ-O)L]2, were obtained by partial evaporation of the solvent during four days. HL and [VO(µ-O)L]2 were characterized by spectroscopic methods and the structure of [VO(µ-O)L]2 was determined by single crystal X-ray analysis which showed that it is a neutral binuclear oxidovanadium(V) coordination compound and is crystallized in triclinic system (P-1 space group). In the unit cell there are two kinds of independent centrosymmetric dinuclear [VO(µ-O)L]2 molecules and the V(V) ions in both molecules are six coordinated. Due to the presence of free amine functional group in the structure, [VO(µ-O)L]2 was supported on the surface of graphene oxide, and a heterogeneous catalyst (GO-V) was provided. GO-V was characterized by FT-IR, UV-DRS, TGA, XRD, FE-SEM, EDX/map and BET analyses. The obtained heterogeneous catalyst was used in the oxidation of benzyl alcohol, and during this process, the effect of influencing parameters was investigated. The catalyst was recovered after the catalytic process and characterized by FT-IR, XRD, FE-SEM and EDX/map analyses. The results indicated that GO-V has high stability and activity in the catalytic conversion of benzyl alcohol to its oxidized products.